Оценка рассчетных воздействий в параболических системах. L₂-подход - Бондарев, В.В. (Український математичний журнал, 1996)
By using observations of solutions of the first initial boundary-value problem for a parabolic quasilinear equation with fast random oscillations, we estimate the nonlinear term of the equation. In the metric of the space L₂, we study large deviations of a nonparametric estimate of nonlinear influence.